2013
DOI: 10.1590/s1806-83242013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Marginal microleakage of class V resin-based composite restorations bonded with six one-step self-etch systems

Abstract: This study compared the microleakage of class V restorations bonded with various one-step self-etching adhesives. Seventy class V resin-based composite restorations were prepared on the buccal and lingual surfaces of 35 premolars, by using: Clearfil S 3 Bond, G-Bond, iBond, One Coat 7.0, OptiBond All-In-One, or Xeno IV. The Adper Single Bond etch-and-rinse two-step adhesive was employed as a control. Specimens were thermocycled for 500 cycles in separate water baths at 5°C and 55°C and loaded under 40 to 70 N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
(48 reference statements)
1
14
0
1
Order By: Relevance
“…When comparing group I and II (both gingivaly and occulsally), the results showed no significant differences between groups. This finding is in agreement with the study of Sánchez et al (23). Moreover, El Sayed et al (24) concluded that although all adhesive systems exhibited dye penetration at both occlusal and gingival margins, etch and rinse systems are still considered a gold standard for adhesion.…”
Section: Disscusionsupporting
confidence: 89%
“…When comparing group I and II (both gingivaly and occulsally), the results showed no significant differences between groups. This finding is in agreement with the study of Sánchez et al (23). Moreover, El Sayed et al (24) concluded that although all adhesive systems exhibited dye penetration at both occlusal and gingival margins, etch and rinse systems are still considered a gold standard for adhesion.…”
Section: Disscusionsupporting
confidence: 89%
“…Contrariamente, se reportan que los sistemas adhesivos autoacondicionadores, independientemente de la orientación de los túbulo, de la profundidad cavitaria y de la ubicación dentinaria (central y periférica), logran en dentina, imprimar las fibras colágenas significativamente mejor en comparación con los adhesivos de grabado independiente 18,19 . Así mismo, coincidentemente en otras publicaciones, no encontraron diferencias significativas en el comportamiento en los adhesivos autoacondicionadores aplicados tanto en esmalte como en dentina sobre todo con los adhesivos que se aplican en dos pasos mediante ensayos de resistencia adhesiva al corte 20,21 . Sin embargo el rendimiento de los adhesivos autoacondicionadores de ultimas generaciones ven comprometidas las uniones adhesivas por la presencia de barro dentinario y por el tiempo de aplicación 22 .…”
Section: Discussionunclassified
“…When adhesive first applied the solvents of the adhesives evaporates and the concentration of the monomers increased for each layer and thereby the quality of hybrid layer improves. Acetone is a solvent and presented with ethanol in optibond [14,20,21]. Two of them may balance the solvent evaporation without dehydrating dentin, because acetone volatilizes rapidly and dehydrates the dentin and ethanol ensures the wetness of the substrate.…”
Section: Discussionmentioning
confidence: 99%